8.03.004: Gerald Squires, "The Newfoundland Landscape 1988-1993:" Letter and program, 1993 - Squires, Gerald, 1937- (Division of University Relations for the Memorial University Art Gallery, 1993)
Page 4 shows "The House Where Nobody Lives." Gerry and I had joked that this painting should be called "Sheep shit and loneliness" and that nearly became the title and cover painting for "Battery Included." Exhibition/Education Curator; Caroline Stone. Includes essay: Michael Cook, "Blind heaven, naked rock : Gerald Squires, some thoughts on his work, in place and time."